Guérison et ethno-étiologie populaire - Brunel, Gilles; Morissette, Luc (Anthropologica, 2022)
This paper is based on anthropological field-work done in Quebec during 1976-1977. It describes the life-history of two folk-healers and their will to achieve better results. Special emphasis is given to their principles of classification of diseases. Such principles agree with those obtained in folk biology. Finally the research stresses the increasing importance of religious syncretism in folk healing systems.